A Well‐Defined Pd Hybrid Material for the Z‐Selective Semihydrogenation of Alkynes Characterized at the Molecular Level by DNP SENS1. Issue 37 (19th August 2013) - Conley, Matthew P.; Drost, Ruben M.; Baffert, Mathieu; Gajan, David; Elsevier, Cornelis; Franks, W. Trent; Oschkinat, Hartmut; Veyre, Laurent; Zagdoun, Alexandre; Rossini, Aaron; Lelli, Moreno; Lesage, Anne; et al.
<x xml:space="preserve">Abstract</x> Direct evidence of the conformation of a Pd–N heterocyclic carbene (NHC) moiety imbedded in a hybrid material and of the Pd–NHC bond were obtained by dynamic nuclear polarization surface‐enhanced NMR spectroscopy (DNP SENS) at natural abundance in short experimental times (hours). Overall, this silica‐based hybrid material containing well‐defined Pd–NHC sites in a uniform environment displays high activity and selectivity in the semihydrogenation of alkynes into Z‐alkenes (see figure).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>